Dirac neutrinos in an SU(2) left-right symmetric model - Diaz, Henry; Pleitez, V. [UNESP]; Ravinez, O. Pereyra (American Physical Society (APS), 2020)
We propose a left-right symmetric model, with the scalar sector consisting of two doublets and several bidoublets, in which neutrinos remain as Dirac fermions in all orders in perturbation theory. Although with only two bidoublets the neutrino masses still need a ne-tuning, this is not the case when a third bidoublet is added. One of the scalar doublets may be inert, since the left-right symmetry forbids it to couple with fermions.